An Integrated Theoretical and Empirical Analysis of Push and Pull Factors in Afghan Irregular Migration: Insights for Sustainable Policy Responses (Salam International Academic Journal, 2025)
Irregular migration from Afghanistan persists as a critical socio-political and economic issue affecting both origin and destination countries. Despite extensive empirical studies, the lack of theoretical integration has hindered comprehensive understanding of the multidimensional drivers of Afghan migration. This study employs, mixed-methods approach, grounded in Lee's Push-Pull Theory Dependency Theory, and Functionalism to analyze the factors influencing Afghan irregular migration and returnee reintegration. Data were collected from 150 returnees originating from Iran, Pakistan, and selected European countries through structured surveys and in-depth interviews. The findings reveal that economic instability, insecurity, and lack of access to essential services are dominant push factors, while employment prospects, social networks, and legal protections in host countries serve as strong pull factors. Reintegration challenges such as unemployment, social stigmatization, and persistent insecurity significantly contribute to a high propensity for re-migration among returnees. The study underscores the need for inclusive development policies, strengthened regional migration governance, and targeted reintegration strategies. These insights provide valuable direction for policymakers seeking to manage migration sustainably and support returnees effectively.
Keywords: Afghan Irregular Migration; Push and Pull Factors; Migration Theories; Returnee Reintegration; Migration Policy; Regional Governance